Improving focality and consistency in micromagnetic stimulation - Ye, Hui; Hall, Vincent; Hendee, Jenna (Frontiers in Computational Neuroscience, 2023)
The novel micromagnetic stimulation (µMS) technology aims to provide high resolution on neuronal targets. However, consistency of neural activation could be compromised by a lack of surgical accuracy, biological variation, and human errors in operation. We have recently modeled the activation of an unmyelinated axon by a circular micro-coil. Although the coil could activate the axon, its performance sometimes lacked focality and consistency. The site of axonal activation could shift by several experimental factors, including the reversal of the coil current, displacement of the coil, and changes in the intensity of the stimulation. Current clinical practice with transcranial magnetic stimulation (TMS) has suggested that figure-eight coils could provide better performance in magnetic stimulation than circular coils. Here, we estimate the performance of µMS by a figure-eight micro-coil, by exploring the impact of the same experimental factors on its focality and consistency in axonal activation. We derived the analytical expression of the electric field and activating function generated by the figure-eight micro-coil, and estimated the location of axonal activation. Using NEURON modeling of an unmyelinated axon, we found two different types (A and B) of axon activation by the figure-eight micro-coil, mediated by coil currents of reversed direction. Type A activation is triggered by membrane hyperpolarization followed by depolarization; Type B activation is triggered by direct membrane depolarization. Consequently, the two types of stimulation are governed by distinct ion channel mechanisms. In comparison to the circular micro-coil, the figure-eight micro-coil requires significantly less current for axonal activation. Under figure-eight micro-coil stimulation, the site of axonal activation does not change with the reversal of the coil current, displacement of the coil, or changes in the intensity of the stimulation. Ultimately, the figure-eight micro-coil provides a more efficient and consistent site of activation than the circular micro-coil in µMS.